Higiene Sanitasi Kapal Dalam Negeri dan Luar Negeri - Hanifatul Mukaromah; Syifaul Lailiyah (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2018)
Abstract: Hygiene and Sanitation of Ships Domestically and Abroad. Sea transportation is still an alternative choice in addition to land and air transport because it has several advantages such as greater haulage and lower cost. Along with technological developments, the ship becomes a transport for travel within and outside the country. Probolinggo Sea Port is one of the domestic and international crossing services for passengers and loading and unloading of goods. Supervision of domestic and overseas ship arrivals is aimed at preventing all risk factors of PHEIC (Public Health Emergency of International Concern), especially ships coming from infected areas. This study aims to describe the hygiene of sanitary ships in the country and abroad at the Port of Probolinggo using an observational method with descriptive approach. Sampling in this study using accidental sampling method with the ratio of overseas and domestic ships is 1: 5. The result showed that there were 46,67% aspect which have not fulfill sanitation hygiene requirement on domestic ship that is 80% medical facility, 60% waste, 20% kitchen, 10% food raft room, 10% machine room, 10% food and 10% garbage. While sanitation hygiene on overseas ships inspected 100% has met the requirements on all aspects. In conclusion, domestic and overseas ships are at low risk of transmitting diseases and have differences in meeting the requirements on all aspects examined especially aspects of medical facilities.